Method for catalyzing alternate copolymerization reaction of epoxide and cyclic anhydride
By mixing the zinc dicarboxylate catalyst with a metal hydrogen compound and grinding it to prepare a composite catalyst, the problems of low catalytic activity and poor selectivity in the prior art are solved, and the high-efficiency oligomer content effect of alternating copolymerization of epoxides and cyclic anhydrides is achieved.
Patent Information
- Application Number
- CN202411133797.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the prior art, when a variety of metal complexes are used to catalyze alternating copolymerization of epoxides and cyclic anhydrides, the catalytic activity is lower and the selectivity is poor, resulting in a higher polyether content.
By mixing the zinc dicarboxylate catalyst with a metal hydrogen compound at a certain molar ratio, and crushing and grinding through a planetary ball mill at high speed, a composite catalyst is prepared, which is used for alternating copolymerization of epoxides and cyclic anhydrides.
The activity and selectivity of the catalyst are significantly improved, the polyether content is reduced, and the efficiency of alternating copolymerization reaction is improved.
Smart Images

Figure CN119591851A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic preparation of polyester materials and relates to a method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride. Background Art
[0002] Traditional polyester materials are mainly divided into semi-aromatic polyesters and aliphatic polyesters. Semi-aromatic polyesters such as polyester polyester are widely used in the fields of fibers, packaging materials and liquid crystal materials due to their excellent mechanical properties, barrier properties and other properties. The monomers used to synthesize aliphatic polyesters come from a large number of renewable resources, and aliphatic polyesters are also a class of excellent degradable materials, so they have attracted much attention and can replace traditional petroleum-based polymers. There are two main methods for synthesizing polyesters. One is the step-by-step polymerization represented by diols and dibasic acids or dibasic esters, and the other is the chain polymerization including the alternating polymerization of epoxides and cyclic anhydrides. Due to the problem of small molecular by-products in step-by-step polymerization, high temperature and low pressure are often required to remove small molecular by-products during the polymerization process to increase the degree of reaction. Therefore, this method has problems such as high energy consumption and difficult control of polymer molecular weight and its distribution. Chain polymerization can use the selectivity of the catalyst to control the structure, molecular weight and its distribution of the polymer. Nowadays, the alternating copolymerization of epoxides and cyclic anhydrides is an emerging way to prepare new polyesters, involving a wide range of monomers, including monomers from many renewable sources. Among them, bio-based epoxides include limonene epoxide, furfural-based epoxide and epoxides derived from vegetable oils, which can be obtained from vegetable oils and non-food plant resources such as corn cobs or straw. At the same time, these polyesters are functionalized through post-polymerization modification, so that they can eventually become new materials with different functions.
[0003] At present, a variety of metal complexes have been used to catalyze the alternating copolymerization of epoxides and cyclic anhydrides, including zinc, magnesium, iron, chromium, manganese, aluminum, nickel and cobalt complexes. Meng et al. (RSC Advances, 2014, 4, 9503) used zinc glutarate as a catalyst to synthesize an alternating copolymer of propylene oxide and phthalic anhydride. The yield of polymerization for 15 hours reached 18.1g polymer / g catalyst (equivalent to 9.65g polymer / g catalyst / 8 hours), and the polyether content was 51%. The zinc dicarboxylate catalyst prepared by this method has a low preparation cost, but has obvious problems of low catalytic activity and poor selectivity.
[0004] The present invention finds that a composite catalyst prepared by mixing a zinc dicarboxylate catalyst and a metal hydrogen compound in a certain molar ratio and grinding the mixture can be applied to the alternating copolymerization of epoxides and cyclic anhydrides, which can significantly improve the catalyst activity and selectivity and reduce the polyether content. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a composite dicarboxylic acid zinc catalyst, which is used to catalyze the alternating copolymerization of epoxides and cyclic anhydrides and has the characteristics of high catalytic activity and low polyether content.
[0006] The technical solution of the present invention is:
[0007] A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride, specifically using a composite dicarboxylic acid zinc catalyst to catalyze the epoxide and cyclic anhydride Alternating copolymerization reaction, wherein n is 1, 2 or 3; R1 and R2 are epoxy compound substituents; R3 and R4 are anhydride substituents; the composite dicarboxylic acid zinc catalyst comprises a main catalyst and a co-catalyst, the main catalyst is a zinc compound with Zn-R(COO)2 as the main body, and the co-catalyst is a metal hydrogen compound XH Y , wherein R is a C1-C8 hydrocarbon group, X is Li, Na, Mg, K, Ca, Be, Sr, Ba, Ra, Fr, Rb or Cs, and Y is 1, 2 or 3.
[0008] Furthermore, R1 and R2 are H, CH2Cl, CH2OBn, methyl, benzene ring, cyclohexene, cyclopentene, naphthalene or cyclohexyl, and R1 and R2 are the same or different; R3 and R4 are H, =CH2, benzene ring, cyclohexene or norbornene ring, and R3 and R4 are the same or different.
[0009] Further, the epoxide is propylene oxide, ethylene oxide, cyclohexene oxide, butylene oxide, epichlorohydrin, phenyl glycidyl ether, allyl glycidyl ether, 2-(ethylene oxide ethoxy)tetrahydro-2H-pyran, tetrahydrofuran or styrene oxide; the cyclic anhydride is succinic anhydride, phthalic anhydride, cyclopentane-1,2-dicarboxylic anhydride, cyclopropane-1,2-dicarboxylic anhydride, itaconic anhydride, citraconic anhydride, maleic anhydride or nadic anhydride.
[0010] Furthermore, the preparation method of the composite dicarboxylic acid zinc catalyst comprises the following steps: firstly mixing the zinc compound and the metal hydrogen compound according to the molar ratio, and grinding them at high speed in an inert atmosphere using a planetary ball mill for 5 to 40 hours at a grinding speed of 100 to 400 rpm to obtain the composite catalyst.
[0011] Furthermore, the molar ratio of the zinc compound to the metal hydrogen compound is 1:0.1-12.
[0012] Furthermore, the copolymerization reaction temperature is 20 to 120° C., and the reaction time is 2 to 100 hours.
[0013] Furthermore, the preparation method of the zinc compound is:
[0014] After mixing the dicarboxylic acid and the zinc source in a molar ratio of 100:20-100, add an appropriate amount of reaction medium (such as dibutyl ether, toluene, tetrahydrofuran and ethanol, etc.), and react at 0-80°C under vigorous stirring conditions for 1-24 hours. Then, after rotary evaporation, washing, filtering and drying, a white powdery product is finally obtained. The zinc source is one or more of zinc oxide, zinc acetate, zinc nitrate, zinc hydroxide, zinc stearate and dialkyl zinc, and the acid source is a dicarboxylic acid R(COOH)2, wherein R is a C1-C8 hydrocarbon group;
[0015] The preferred preparation method is as follows: a dialkyl zinc solution is added to a dicarboxylic acid solution, the reaction is carried out under a specific temperature increase program, a crude dicarboxylic acid zinc catalyst is synthesized by a precipitation method, and finally the dicarboxylic acid zinc catalyst is obtained by washing, filtering and drying. The purity of the dicarboxylic acid zinc catalyst is ≥99%. The specific temperature increase program refers to: the dialkyl zinc solution and the dicarboxylic acid solution are prepared at a low temperature, the initial temperature of the two after mixing is -5 to 10°C, and the temperature is increased to room temperature at a heating rate of 0.1 to 1°C / min.
[0016] Further, the dialkyl zinc is (C x H 2x+1 )2Zn; the good solvent of the reaction system of dialkyl zinc and dicarboxylic acid R(COOH)2 is C x H 2x+1 OH, C x H 2x+2 , C x H 2x+1 COC x H 2x+1 , C x H 2x+1 OC x H 2x+1 and C x H 2x O y One or a mixture of two or more of the following, wherein R is a 1-C8 hydrocarbon group, x≥1, y≥1; and the dicarboxylic acid is one of succinic acid, glutaric acid, adipic acid, pimelic acid or suberic acid.
[0017] Furthermore, the molar ratio of dialkyl zinc to dicarboxylic acid is 20:20-22; the mass concentration of the dialkyl zinc solution is 10%-20%; the mass concentration of the dicarboxylic acid solution is 5%-15%; the reaction time under a specific temperature rising program is 1-12 hours, and mechanical stirring is performed at a rotation speed of 0-3000 rpm during the reaction.
[0018] Furthermore, the XRD spectrum of the prepared zinc compound has diffraction peaks at 2θ angles of 12.90±0.5, 22.80±0.4, and 23.10±0.4, the full width at half maximum is higher than 0.4, the crystallinity is 40-70%, and the specific surface area of the zinc dicarboxylate catalyst is 30-100m 2 / g.
[0019] Furthermore, the epoxide and the cyclic anhydride are alternately copolymerized: an appropriate amount of the composite catalyst is dissolved in a solvent, and then the epoxide and the cyclic anhydride are added separately, and the reaction temperature and reaction time are set. After the reaction is completed, the solvent is removed by rotary evaporation, the viscous product is taken out, dichloromethane is added to stir and dissolve, and 5% hydrochloric acid is added to remove the residual zinc compound catalyst, acid anhydride and metal hydrogen compound, and then methanol is added for washing, and finally the alternating copolymerization product is obtained by drying. The molar ratio of zinc compound, epoxide and cyclic anhydride is 1:100~600:1~100. The beneficial effects of the present invention are:
[0020] The composite catalyst prepared by the invention has a simple preparation method, is applied to catalyze the alternating copolymerization reaction of epoxide and cyclic anhydride, and has the characteristics of high catalytic activity and low polyether content. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 For the preparation of copolymer in Comparative Example 1 1 H NMR spectrum;
[0022] Figure 2 The copolymer prepared in Example 1 1 H NMR spectrum;
[0023] Figure 3 The copolymer prepared in Example 2 1 H NMR spectrum;
[0024] Figure 4 The copolymer prepared in Example 3 1 H NMR spectrum;
[0025] Figure 5 The copolymer yields and 1 Histogram of H NMR spectra; DETAILED DESCRIPTION
[0026] The present invention is described in detail below with reference to the embodiments.
[0027] Embodiment 1:
[0028] Take 20mmol glutaric acid to prepare a tetrahydrofuran solution with a mass concentration of about 15%, then add it to a 100ml round-bottom flask, set the rotation speed to 1000rpm, slowly add a 20% n-hexane solution with 20mmol diethyl zinc dissolved in it under a 0℃ nitrogen environment, and after adding, heat it from 0℃ to room temperature at a rate of 0.2℃ / min, and react for 6 hours. After the reaction, remove the unreacted diethyl zinc and glutaric acid with n-hexane and tetrahydrofuran respectively, and obtain a zinc glutarate catalyst after drying. In a nitrogen atmosphere, premix zinc glutarate with sodium hydride at a molar ratio of 1:0.5, and grind it in a planetary ball mill for 30 hours at a speed of 300 rpm to prepare a composite catalyst. Add the corresponding composite catalyst (the main catalyst is 0.92mmol) to a 100ml round-bottom flask, then add an appropriate amount of toluene, then add propylene oxide and phthalic anhydride to the flask respectively (the molar ratio of zinc glutarate, propylene oxide and phthalic anhydride is 1:311:39), set the reaction temperature to 75°C, and react for 8 hours. After the reaction is completed, remove the solvent by rotary evaporation, take out the viscous product from the reaction bottle, add dichloromethane to stir and dissolve, and add 5% hydrochloric acid to remove the residual catalyst, acid anhydride and metal hydrogen compound, then add methanol to wash, and finally dry to obtain the copolymer. Figure 2 The copolymer prepared in Example 1 1 H NMR spectrum.
[0029] Embodiment 2:
[0030] Take 20mmol glutaric acid to prepare a tetrahydrofuran solution with a mass concentration of about 15%, then add it to a 100ml round-bottom flask, set the rotation speed to 1000rpm, slowly add a 20% n-hexane solution with 20mmol diethyl zinc dissolved in it under a 0℃ nitrogen environment, and after adding, heat it from 0℃ to room temperature at a rate of 0.2℃ / min, and react for 6 hours. After the reaction is completed, remove the unreacted diethyl zinc and glutaric acid with n-hexane and tetrahydrofuran respectively, and obtain a zinc glutarate catalyst after drying. In a nitrogen atmosphere, premix zinc glutarate with sodium hydride in a molar ratio of 1:3, and grind it in a planetary ball mill for 30 hours at a ball mill speed of 300 rpm to prepare a composite catalyst. Add the corresponding composite catalyst (the main catalyst is 0.92mmol) to a 100ml round-bottom flask, then add an appropriate amount of toluene, then add propylene oxide and phthalic anhydride to the flask respectively (the molar ratio of zinc glutarate, propylene oxide and phthalic anhydride is 1:311:39), set the reaction temperature to 75°C, and react for 8 hours. After the reaction is completed, remove the solvent by rotary evaporation, take out the viscous product from the reaction bottle, add dichloromethane to stir and dissolve, and add 5% hydrochloric acid to remove the residual catalyst, acid anhydride and metal hydrogen compound, then add methanol to wash, and finally dry to obtain the copolymer. Figure 3The copolymer prepared in Example 2 1 H NMR spectrum.
[0031] Embodiment 3:
[0032] Take 20mmol glutaric acid to prepare a tetrahydrofuran solution with a mass concentration of about 15%, then add it to a 100ml round-bottom flask, set the rotation speed to 1000rpm, slowly add a 20% n-hexane solution with 20mmol diethyl zinc dissolved in it under a 0℃ nitrogen environment, and after adding, heat it from 0℃ to room temperature at a rate of 0.2℃ / min, and react for 6 hours. After the reaction is completed, remove the unreacted diethyl zinc and glutaric acid with n-hexane and tetrahydrofuran respectively, and obtain a zinc glutarate catalyst after drying. In a nitrogen atmosphere, premix zinc glutarate with sodium hydride in a molar ratio of 1:6, and grind it in a planetary ball mill for 30 hours at a speed of 300 rpm to prepare a composite catalyst. Add the corresponding composite catalyst (the main catalyst is 0.92mmol) to a 100ml round-bottom flask, then add an appropriate amount of toluene, then add propylene oxide and phthalic anhydride to the flask respectively (the molar ratio of zinc glutarate, propylene oxide and phthalic anhydride is 1:311:39), set the reaction temperature to 75°C, and react for 8 hours. After the reaction is completed, remove the solvent by rotary evaporation, take out the viscous product from the reaction bottle, add dichloromethane to stir and dissolve, and add 5% hydrochloric acid to remove the residual catalyst, acid anhydride and metal hydrogen compound, then add methanol to wash, and finally dry to obtain the copolymer. Figure 4 The copolymer prepared in Example 3 1 H NMR spectrum.
[0033] Embodiment 4:
[0034] Take 20mmol adipic acid to prepare a tetrahydrofuran solution with a mass concentration of about 5%, then add it to a 100ml round-bottom flask, set the speed to 1000rpm, slowly add a 10% n-hexane solution with 20mmol diisopropyl zinc dissolved in a 10% mass concentration under a 10℃ nitrogen environment, and after adding, heat from 10℃ to room temperature at a rate of 0.9℃ / min, and react for 1 hour. After the reaction, remove the unreacted diisopropyl zinc and adipic acid with n-hexane and tetrahydrofuran respectively, and obtain a zinc adipate catalyst after drying. In a nitrogen atmosphere, zinc adipate and potassium hydride are premixed in a molar ratio of 1:10, and then ground in a planetary ball mill for 5h, with a ball mill speed of 100 rpm, to prepare a composite catalyst. The corresponding composite catalyst (main catalyst is 0.86 mmol) is added to a 100 ml round-bottom flask, and then an appropriate amount of toluene is added, and then propylene oxide and maleic anhydride are added to the flask respectively (the molar ratio of zinc adipate, propylene oxide and maleic anhydride is 1:333:42), and the reaction temperature is set to 75 ° C. The reaction is carried out for 8 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the viscous product is taken out from the reaction bottle, and dichloromethane is added to stir and dissolve, and 5% hydrochloric acid is added to remove the residual catalyst, anhydride and metal hydrogen compound, and then methanol is added for washing, and finally the copolymer is obtained after drying.
[0035] Embodiment 5:
[0036] Take 100mmol of zinc oxide (99.9%), 100mmol of glutaric acid (99.0%), and 250ml of toluene, add them to a 500ml three-necked flask, react for 24h under vigorous stirring at 55℃, remove toluene by rotary evaporation after the reaction, wash with acetone several times, and dry to obtain zinc glutarate catalyst. In a nitrogen atmosphere, zinc glutarate and calcium hydride are premixed in a molar ratio of 1:4, and then ground by a planetary ball mill for 30h at a ball mill speed of 300 rpm to prepare a composite catalyst. Add the corresponding composite catalyst (main catalyst is 0.92mmol) to a 100ml round-bottom flask, add an appropriate amount of toluene, and then add ethylene oxide and phthalic anhydride to the flask respectively (the molar ratio of zinc glutarate, ethylene oxide and phthalic anhydride is 1:435:54), set the reaction temperature to 50℃, and react for 8 hours. After the reaction, the solvent was removed by rotary evaporation, the viscous product was taken out from the reaction bottle, dichloromethane was added to stir and dissolve, and 5% hydrochloric acid was added to remove the residual catalyst, acid anhydride and metal hydrogen compound, and then methanol was added for washing, and finally the copolymer was obtained by drying.
[0037] Embodiment 6:
[0038] Take 100mmol of zinc oxide (99.9%), 100mmol of adipic acid (99.0%), and 250ml of toluene, add them to a 500ml three-necked flask, react for 24h under vigorous stirring at 55℃, remove toluene by rotary evaporation after the reaction, wash with acetone several times, and dry to obtain zinc adipate catalyst. In a nitrogen atmosphere, zinc adipate and sodium hydride are premixed in a molar ratio of 1:6, and then ground by a planetary ball mill for 30h at a ball mill speed of 300 rpm to prepare a composite catalyst. Add the corresponding composite catalyst (main catalyst is 0.86mmol) to a 100ml round-bottom flask, add an appropriate amount of toluene, and then add propylene oxide and succinic anhydride to the flask respectively (the molar ratio of zinc adipate, propylene oxide and succinic anhydride is 1:333:42), set the reaction temperature to 75℃, and react for 8 hours. After the reaction, the solvent was removed by rotary evaporation, the viscous product was taken out from the reaction bottle, dichloromethane was added to stir and dissolve, and 5% hydrochloric acid was added to remove the residual catalyst, acid anhydride and metal hydrogen compound, and then methanol was added for washing, and finally the copolymer was obtained by drying.
[0039] Comparative Example 1 (compared with Examples 1, 2, and 3):
[0040] Take 20mmol glutaric acid and configure it into a tetrahydrofuran solution with a mass concentration of about 15%, then add it to a 100ml round-bottom flask, set the speed to 1000rpm, slowly add a 20% n-hexane solution with a mass concentration of 20mmol diethyl zinc dissolved in a 0℃ nitrogen environment, and after adding, heat up from 0℃ to room temperature at a rate of 0.2℃ / min, and react for 6 hours. After the reaction is completed, remove the unreacted diethyl zinc and glutaric acid with n-hexane and tetrahydrofuran, respectively, and obtain a zinc glutarate catalyst after drying. Under a nitrogen atmosphere, the zinc glutarate catalyst is ground for 30h using a planetary ball mill, and the ball mill speed is 300 rpm. Add 0.92mmol of the ground zinc glutarate catalyst to a 100ml round-bottom flask, add an appropriate amount of toluene, and then add propylene oxide and phthalic anhydride to the bottle (the molar ratio of zinc glutarate, propylene oxide and phthalic anhydride is 1:311:39), set the reaction temperature to 75℃, and react for 8 hours. After the reaction, the solvent was removed by rotary evaporation, the viscous product was taken out from the reaction bottle, dichloromethane was added to stir and dissolve, and 5% hydrochloric acid was added to remove the residual catalyst and acid anhydride, and then methanol was added for washing, and finally the copolymer was obtained by drying. Figure 1 The copolymer prepared in Comparative Example 1 1 H NMR spectrum.
[0041] Comparative Example 2 (compared with Examples 1, 2, and 3):
[0042] Take 20mmol glutaric acid to prepare a tetrahydrofuran solution with a mass concentration of about 15%, then add it to a 100ml round-bottom flask, set the rotation speed to 1000rpm, slowly add a 20% n-hexane solution with 20mmol diethyl zinc dissolved in it under a 0℃ nitrogen environment, and after adding, heat it from 0℃ to room temperature at a rate of 0.2℃ / min, and react for 6 hours. After the reaction is completed, remove the unreacted diethyl zinc and glutaric acid with n-hexane and tetrahydrofuran respectively, and obtain a zinc glutarate catalyst after drying. In a nitrogen atmosphere, premix zinc glutarate with sodium hydride in a molar ratio of 1:15, and grind it in a planetary ball mill for 30 hours at a ball mill speed of 300 rpm to prepare a composite catalyst. The corresponding composite catalyst (main catalyst is 0.92mmol) is added to a 100ml round-bottom flask, and then an appropriate amount of toluene is added, and then propylene oxide and phthalic anhydride are added to the flask respectively (the molar ratio of zinc glutarate, propylene oxide and phthalic anhydride is 1:311:39), and the reaction temperature is set to 75°C, and the reaction is carried out for 8 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the viscous product is taken out from the reaction bottle, and dichloromethane is added to stir and dissolve, and 5% hydrochloric acid is added to remove the residual catalyst, anhydride and metal hydrogen compound, and then methanol is added for washing, and finally the copolymer is obtained after drying.
[0043] Comparative Example 3 (compared with Example 5):
[0044] Take 100mmol of zinc oxide (99.9%), 100mmol of glutaric acid (99.0%), and 250ml of toluene, add them to a 500ml three-necked flask, react for 24h under vigorous stirring at 55°C, remove toluene by rotary evaporation after the reaction, wash with acetone several times, and finally dry to obtain a zinc glutarate catalyst. In a nitrogen atmosphere, the zinc glutarate catalyst is ground for 30h using a planetary ball mill at a ball mill speed of 300 rpm. Add 0.92mmol of the ground zinc glutarate catalyst to a 100ml round-bottom flask, add an appropriate amount of toluene, and then add ethylene oxide and phthalic anhydride to the flask respectively (the molar ratio of zinc glutarate, ethylene oxide and phthalic anhydride is 1:435:54), set the reaction temperature to 50°C, and react for 8 hours. After the reaction, the solvent was removed by rotary evaporation, and the viscous product was taken out from the reaction bottle. Dichloromethane was added to stir and dissolve, and 5% hydrochloric acid was added to remove the residual catalyst and acid anhydride. Then methanol was added for washing, and finally the copolymer was obtained by drying.
[0045] Comparative Example 4 (compared with Example 6):
[0046] Take 100mmol of zinc oxide (99.9%), 100mmol of adipic acid (99.0%), and 250ml of toluene, add them to a 500ml three-necked flask, react for 24h under vigorous stirring at 55℃, remove toluene by rotary evaporation after the reaction, wash with acetone several times, and dry to obtain zinc adipate catalyst. In a nitrogen atmosphere, the zinc adipate catalyst is ground for 30h using a planetary ball mill at a speed of 300 rpm. Add 0.86mmol of ground zinc adipate catalyst to a 100ml round-bottom flask, add an appropriate amount of toluene, and then add propylene oxide and succinic anhydride to the flask respectively (the molar ratio of zinc adipate, propylene oxide and succinic anhydride is 1:333:42), set the reaction temperature to 75℃, and react for 8 hours. After the reaction, the solvent was removed by rotary evaporation, and the viscous product was taken out from the reaction bottle. Dichloromethane was added to stir and dissolve, and 5% hydrochloric acid was added to remove the residual catalyst and acid anhydride. Then methanol was added for washing, and finally the copolymer was obtained by drying.
[0047] The catalysts in the above examples and comparative examples were used to catalyze the preparation of alternating copolymers. The polymerization results are shown in Table 1:
[0048] Table 1
[0049]
[0050]
[0051] Examples 1-6 and Comparative Examples 1-4 are the results of applying composite dicarboxylic acid zinc catalysts to the alternating copolymerization of propylene oxide or ethylene oxide and itaconic anhydride, phthalic anhydride, succinic anhydride or maleic anhydride.
[0052] As shown in Table 1, the zinc compound catalysts of Examples 1, 2, 3, 4 and Comparative Examples 1 and 2 are derived from the preferred preparation method, and the zinc compound catalysts of Examples 5 and 6 and Comparative Examples 3 and 4 are derived from the general preparation method. The composite catalysts obtained by compounding the zinc compound catalysts prepared by these two methods with metal hydrogen compounds are applied to catalyze the alternating copolymerization of epoxides and cyclic anhydrides, and their activity and selectivity are higher than those of the single catalysts prepared by the respective methods. Compared with Comparative Examples 1 and 2, Examples 1, 2, and 3 use the same zinc compound catalyst and metal hydrogen compound for compounding, and different molar ratios have a greater impact on activity and selectivity. When an appropriate amount of metal hydrogen compound is used to compound the zinc compound catalyst, its activity and selectivity are significantly improved. Compared with Comparative Example 1, the activities of Examples 1, 2, and 3 are increased by 19.4%, 59.7%, and 71.8%, respectively, and the polyester content is increased by 3.2%, 6.9%, and 11%, respectively. However, when an excessive amount of metal hydrogen compound is used for compounding, its activity and selectivity are significantly reduced, so the appropriate molar ratio is particularly critical for activity and selectivity. The reason why Comparative Examples 1 and 2 have better effects than Examples 5 and 6 is that the zinc compound catalyst prepared by the preferred method for preparing the zinc compound catalyst is much better than the zinc compound catalyst prepared by the general preparation method.
[0053] The invention discloses a method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride. The composite catalyst is prepared by ball milling a zinc compound catalyst and a metal hydrogen compound to catalyze the alternating copolymerization reaction. The preparation method is simple. The general formula zinc compound Zn-R(COO)2 (R is a C1-C8 hydrocarbon group) and the general formula metal hydrogen compound XH Y (X is Li, Na, Mg, K, Ca, Be, Sr, Ba, Ra, Fr, Rb or Cs, and Y is 1, 2 or 3) are used together as catalysts, and the yield and polyester content are significantly improved.
[0054] It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. In addition, the above are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
Claims
1. A method for catalyzing the alternating copolymerization of epoxides and cyclic anhydrides, characterized in that: Catalytic production of epoxides using composite dicarboxylic acid zinc catalysts and cyclic anhydride Alternating copolymerization reaction, wherein n is 1, 2 or 3; R1 and R2 are epoxy compound substituents; R3 and R4 are anhydride substituents; the composite dicarboxylic acid zinc catalyst comprises a main catalyst and a co-catalyst, the main catalyst is a zinc compound with Zn-R(COO)2 as the main body, and the co-catalyst is a metal hydrogen compound XH Y , wherein R is a C1-C8 hydrocarbon group, X is Li, Na, Mg, K, Ca, Be, Sr, Ba, Ra, Fr, Rb or Cs, and Y is 1, 2 or 3.
2. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 1, characterized in that: R1 and R2 are H, CH2Cl, CH2OBn, methyl, benzene ring, cyclohexene, cyclopentene, naphthalene or cyclohexyl, and R1 and R2 are the same or different; R3 and R4 are H, =CH2, benzene ring, cyclohexene or norbornene ring, and R3 and R4 are the same or different.
3. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 1, characterized in that: The epoxide is propylene oxide, ethylene oxide, cyclohexene oxide, butylene oxide, epichlorohydrin, phenyl glycidyl ether, allyl glycidyl ether, 2-(ethylene oxide ethoxy)tetrahydro-2H-pyran, tetrahydrofuran or styrene oxide; the cyclic anhydride is succinic anhydride, phthalic anhydride, cyclopentane-1,2-dicarboxylic anhydride, cyclopropane-1,2-dicarboxylic anhydride, itaconic anhydride, citraconic anhydride, maleic anhydride or nadic anhydride.
4. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 1, characterized in that: The preparation method of a composite dicarboxylic acid zinc catalyst comprises the following steps: firstly mixing the zinc compound and the metal hydrogen compound according to the molar ratio, and grinding them at high speed for 5 to 40 hours in an inert atmosphere using a planetary ball mill at a grinding speed of 100 to 400 rpm to obtain a composite catalyst.
5. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 1, characterized in that: The molar ratio of the zinc compound to the metal hydrogen compound is 1:0.1-12.
6. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 1, characterized in that: The copolymerization reaction temperature is 20-120°C, and the reaction time is 2-100h.
7. A method for catalyzing the alternating copolymerization of epoxides and cyclic anhydrides according to any one of claims 1 to 6, characterized in that: The preparation method of the zinc compound comprises the following steps: adding a dialkyl zinc solution to a dicarboxylic acid solution, reacting under a specific temperature increase program, synthesizing a crude dicarboxylic acid zinc catalyst by a precipitation method, and finally washing, filtering and drying to obtain the dicarboxylic acid zinc catalyst, wherein the purity of the dicarboxylic acid zinc catalyst is ≥99%; the specific temperature increase program refers to: preparing the dialkyl zinc solution and the dicarboxylic acid solution at a low temperature, the initial temperature of the two after mixing is -5 to 10°C, and the temperature is increased to room temperature at a temperature increase rate of 0.1 to 1°C / min.
8. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 7, characterized in that: Dialkylzinc is (C x H 2x+1 )2Zn; the good solvent of the reaction system of dialkyl zinc and dicarboxylic acid R(COOH)2 is C x H 2x+1 OH, C x H 2x+2 , C x H 2x+1 COC x H 2x+1 , C x H 2x+1 OC x H 2x+1 and C x H 2x O y One or a mixture of two or more of the above, wherein R is a C1-C8 hydrocarbon group, x≥1, y≥1; and the dicarboxylic acid is one of succinic acid, glutaric acid, adipic acid, pimelic acid or suberic acid.
9. A method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 7, characterized in that: The molar ratio of the dialkyl zinc to the dicarboxylic acid is 20:20-22; the mass concentration of the dialkyl zinc solution is 10%-20%; the mass concentration of the dicarboxylic acid solution is 5%-15%; the reaction time under a specific temperature rise program is 1-12 hours, and mechanical stirring is performed at a rotation speed of 0-3000 rpm during the reaction.
10. The method for catalyzing the alternating copolymerization of epoxide and cyclic anhydride according to claim 7, characterized in that: The XRD spectrum of the prepared zinc compound has diffraction peaks at 2θ angles of 12.90±0.5, 22.80±0.4, and 23.10±0.4, the full width at half maximum is higher than 0.4, and the crystallinity is 40-70%. The specific surface area of the zinc dicarboxylate catalyst is 30-100m 2 / g.
Citation Information
Patent Citations
Compound type zinc dicarboxylate catalyst, and preparation method and application thereof
CN102952264A
Method for preparing zinc dicarboxylate catalyst, modified zinc dicarboxylate catalyst and carbon dioxide-epoxide copolymer
CN105418907A
Method for producing polymeric ring-opening products
CN109890869A
Method for preparing polyester by catalyzing cyclic anhydride / epoxide ring opening alternate copolymerization with potassium acetate
CN111909366A
DES ionic gel as well as preparation method and application thereof
CN118459675A
Cited By
Degradation, recovery and regeneration method of degradable anhydride cured epoxy resin
CN120987797A
A method for degrading and recycling a degradable anhydride-cured epoxy resin
CN120987797B